'A Baby Is a Baby': The Asha Protests and the Sociology of Affective Post-Nationalism. (February 2021) - Tonkiss, Katherine
Theories of post-nationalism are concerned with deconstructing the relationship between citizenship and national identity. While literature in this field has tended towards macro-institutionalist analysis, recent research has re-articulated post-nationalism as micro-level practice. This article builds on this development by attending to the 'affective conditions' of such micro-political practices. The article draws on research into protests in Brisbane in February 2016 to prevent 'Asha', a child seeking asylum, from being returned to offshore detention. The analysis of this case demonstrates that affect performs a dual function in the practice of post-nationalism, to catalyse action in solidarity with the noncitizen informed primarily by the emotional resonance of a particular rendering of vulnerability, and in re-imagined solidarity with the co-citizen around a post-national community of feeling. Informed by this analysis, the article highlights the complex and fragile nature of a post-national solidarity dependent on intersecting, overlapping and at times problematic, affective conditions.